Study on the Application of Cool Paintings for the Passive Cooling of Existing Buildings in Mediterranean Climates. (2nd November 2013) - Costanzo, V.; Evola, G.; Gagliano, A.; Marletta, L.; Nocera, F.
Abstract : Building roofs play a very important role in the energy balance of buildings, especially in summer, when they are hit by a rather high solar irradiance. Depending on the type of finishing layer, roofs can absorb a great amount of heat and reach quite high temperatures on their outermost surface, which determines significant room overheating. However, the use of highly reflectivecool materials can help to maintain low outer surface temperatures; this practice may improve indoor thermal comfort and reduce the cooling energy need during the hot season. This technology is currently well known and widely used in the USA, while receiving increasing attention in Europe. In order to investigate the effectiveness of cool roofs as a passive strategy for passive cooling in moderately hot climates, this paper presents the numerical results of a case study based on the dynamic thermal analysis of an existing office building in Catania (southern Italy, Mediterranean area). The results show how the application of a cool paint on the roof can enhance the thermal comfort of the occupants by reducing the operative temperatures of the rooms and to reduce the overall energy needs of the building for space heating and cooling.